Asking smarter questions : how to be an agent of insight - Knowles, Sam (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Insight is the superpower that drives innovation and enables us to understand the world from other peoples' points of view, be they customers or colleagues, advocates or competitors. This new book from master data storyteller Sam Knowles explains how to ask smarter questions - questions that, by design, stimulate more useful answers. This is the shortcut to better productivity, fast-tracked innovation, and organisational success - for businesses, universities, charities, and governments. For too long, the simple act of asking questions has been overlooked as almost too trivial to contemplate. Asking Smarter Questions seeks to champion the art of curiosity by setting out a framework to make every question count. The fundamental building blocks of insight are data and information, joined together in new and often unpredictable ways. The way we surface new data and information and make meaningful connections between data points is by ... asking smarter questions. By taking this approach, you can make your organisation a less confrontational, more collaborative, and more productive environment in which to work - particularly in the more distributed and remote settings that will characterise the 2020s. Managers, directors, and leaders will find the universal principles, expert interviews, and data-driven recommendations a source of inspiration to share with their teams. Asking Smarter Questions is aimed at professionals in businesses and organisations across all sectors, and will help those working in many functions, including: market research, intelligence, insight, analytics, strategy, marketing, communications, planning, new product development, and innovation"--
OCLC-licensed vendor bibliographic record.
Keywords: Insight; Questioning; Thought and thinking; BUSINESS & ECONOMICS / Business Communication / General; BUSINESS & ECONOMICS / Negotiating; BUSINESS & ECONOMICS / Information Management